Gandhi and the Muslims of India: A Study on the Collected Works of Mahatma Gandhi - Amarjit Singh (European Scientific Journal, ESJ, 2017)
This research paper is essentially selections from the Collected Works of Mahatma Gandhi regarding the approach of Gandhi towards the Muslims of India and his constant efforts for the maintenance of the HinduMuslim unity. This present paper also throws ample light on the relationship which existed between the Indian National Congress and the All India Muslim League and the events leading to the partition of India. This paper covers the period since the involvement of Gandhiji with the Khilafat Conference until that of the martyrdom of Gandhiji at the altar of the HinduMuslim unity. It has been argued in this research paper that the speeches, writings, correspondences, and statements of Gandhiji clearly reveal his deep understanding of the Islam, his love towards the Muslims of India, his heartily desire for the maintenance of the Hindu-Muslim unity and, above all, his love towards humanity. This is without considering the distinction of class, caste, religion, and even nationality.